2008
DOI: 10.2106/jbjs.g.01354
|View full text |Cite
|
Sign up to set email alerts
|

Supracondylar Humeral Fractures in Children

Abstract: Operative fixation is indicated for most type-II and III supracondylar humeral fractures in order to prevent malunion. Medial comminution is a subtle finding that, if treated nonoperatively, is likely to lead to unacceptable varus malunion. Angiography is not indicated for a pulseless limb, as it delays fracture reduction, which usually corrects the vascular problem. A high index of suspicion is necessary to avoid missing an impending compartment syndrome, especially when there is a concomitant forearm fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
408
3
69

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 444 publications
(502 citation statements)
references
References 59 publications
22
408
3
69
Order By: Relevance
“…The pooled result of iatrogenic ulnar nerve injury in the current study is in agreement with previous reviews [1,3,5,38,40,52]. Babal et al [3] performed a meta-analysis which was derived almost exclusively from retrospective studies and concluded that the medial pin carried the greater overall risk of nerve injury as compared with a lateral-pin-only construct, and that the ulnar nerve was at risk of injury in patients who had medial pins.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The pooled result of iatrogenic ulnar nerve injury in the current study is in agreement with previous reviews [1,3,5,38,40,52]. Babal et al [3] performed a meta-analysis which was derived almost exclusively from retrospective studies and concluded that the medial pin carried the greater overall risk of nerve injury as compared with a lateral-pin-only construct, and that the ulnar nerve was at risk of injury in patients who had medial pins.…”
Section: Discussionsupporting
confidence: 91%
“…Skaggs et al [50] retrospectively reviewed the results of reduction and pin fixation of 345 extension-type supracondylar fractures in children and found there was no difference regarding maintenance of fracture reduction between the crossed pins and the lateral pins. Omid et al [40] considered that lateral entry pins could be as stable as crossed pinning in biomechanical and clinical studies if they are well spaced at the fracture line. A systematic review performed by Brauer et al [5] showed that deformity occurred in 3.4% of the patients treated with medial and lateral entry pins and in 5.9% of patients treated with lateral entry pins, therefore concluding that medial and lateral pin entry provides a more stable configuration and the probability of deformity or loss of reduction is 0.58 times lower than with isolated lateral pin entry.…”
Section: Discussionmentioning
confidence: 99%
“…O mecanismo de trauma mais comum é a queda com apoio do membro superior e o cotovelo em extensão completa, levando o olécrano a realizar um fulcro posterior na sua fossa, região de maior fragilidade, provocando uma fratura do tipo em extensão, isto é, com desvio posterior (8,9) . Este tipo de desvio representa cerca de 97% a 99% dos casos (5,8) .…”
Section: Introductionunclassified
“…Contudo, desvios rotacionais são mais difí-ceis de serem avaliados. Atribuem-se às más reduções rotacionais a ocorrência do cúbito varo, influenciando a perda da redução, devido à falta de apoio das colunas medial e lateral (9) .…”
Section: Introductionunclassified
See 1 more Smart Citation